2004
DOI: 10.1038/sj.ejcn.1602072
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma vitamin E levels in major depression: diet or disease?

Abstract: Objective: Levels of vitamin E have been reported to be lower in patients suffering major depression, but whether this is due to inadequate dietary intake or the pathophysiology of depression is not known, and was the subject of the present study. Setting: Wollongong, Australia. Methods: Plasma vitamin E (a-tocopherol) was measured in 49 adults with major depression, age (mean7s.d.): 47712 y. In a subset (n ¼ 19) usual dietary intake of vitamin E was determined by diet history. Results: Subjects had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 14 publications
2
53
1
1
Order By: Relevance
“…Moreover, a significant positive correlation was found between oxidative stress index and the Hamilton Depression Rating Scale (HAMD) (Yanik et al, 2004a). Similarly, other studies have also reported correlations between depressive severity and the magnitude of disturbances in their respective oxidative indices (Bilici et al, 2001 ;Forlenza and Miller, 2006;Owen et al, 2005;Sarandol et al, 2007b), although one study found no such relationship (Herken et al, 2007). The enhanced oxidation of apolipoprotein Bcontaining lipoproteins, correlating with the severity of major depression, along with significant reductions in serum paraoxonase/arylesterase activities following antidepressant treatment, have been demonstrated (Sarandol et al, 2006).…”
Section: Human Assays Of Oxidants Antioxidants and Oxidative Productsmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, a significant positive correlation was found between oxidative stress index and the Hamilton Depression Rating Scale (HAMD) (Yanik et al, 2004a). Similarly, other studies have also reported correlations between depressive severity and the magnitude of disturbances in their respective oxidative indices (Bilici et al, 2001 ;Forlenza and Miller, 2006;Owen et al, 2005;Sarandol et al, 2007b), although one study found no such relationship (Herken et al, 2007). The enhanced oxidation of apolipoprotein Bcontaining lipoproteins, correlating with the severity of major depression, along with significant reductions in serum paraoxonase/arylesterase activities following antidepressant treatment, have been demonstrated (Sarandol et al, 2006).…”
Section: Human Assays Of Oxidants Antioxidants and Oxidative Productsmentioning
confidence: 71%
“…Human studies have reported a number of oxidative disturbances in patients with major depression, including oxidative damage in erythrocytic membranes as suggested by the depletion of omega-3 fatty acids (Peet et al, 1998); elevated lipid peroxidation products (Bilici et al, 2001;Khanzode et al, 2003;Sarandol et al, 2007b;Selley, 2004) ; oxidative DNA damage (Forlenza and Miller, 2006) ; reduced serum vitamins C (Khanzode et al, 2003) and E (Maes et al, 2000;Owen et al, 2005), the latter of which was not accounted for by dietary insufficiency (Owen et al, 2005) ; increased concentrations of the endogenous inhibitor of endothelial NO synthase asymmetric dimethylarginine (ADMA) (Selley, 2004) and decreased NO (Selley, 2004;Srivastava et al, 2002). Albumin, which has antioxidant activity, has also been reported to be compromised in major depression (Van Hunsel et al, 1996).…”
Section: Human Assays Of Oxidants Antioxidants and Oxidative Productsmentioning
confidence: 99%
“…Low plasma vitamin E has been suggested to play a role in the higher rates of membrane lipid peroxidation found in individuals with schizophrenia and depression when compared to controls. 29,30 In a study of an individual who had compound heterozygous apoB mutations, apoB-66 plus apoB-25.8, Homer et al 23 suggested that the clinical presentation, of ataxia, visual impairment and neuropathy, resulted from the inability to transport the active stereoisomer of vitamin E from the liver and that these clinical features were similar to those seen in isolated vitamin E deficiency. Therefore, the index patient's phenotype is intermediate in the spectrum between homozygous FHBL (very low or absent LDL-cholesterol, acanthocytes and sometimes neurological deficit) and other heterozygous FHBL families (no acanthocytes, moderate to low LDL-cholesterol, live longer and have neither functional psychiatric illness nor neurological deficit).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have antioxidant properties. However, supplementation of a-tocopherol (a major antioxidant nutrient) did not reduce depressive status in the elderly although plasma vitamin E was lower in persons with depression (30,31) . It should also be mentioned that although the frequency of intake of vegetables (and maybe fruits and eggs) can predict future risk of depression in longitudinal studies, the possibility of reverse causality still cannot be totally excluded because the relationship between food and mood is bidirectional and both food pattern and depressive symptoms can be affected by events in daily life or the living environment (32) .…”
Section: Potential Mechanismmentioning
confidence: 99%